2020
DOI: 10.21203/rs.3.rs-34884/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA HOXA-AS2 Facilitates Cervical Cancer Progression and Angiogenesis via miR-509-3p/BTN3A1 Axis

Abstract: Background: Cervical cancer, the leading cause of cancer-relevant mortality in females, is an aggressive malignant tumor. Tumor angiogenesis is vital for cell proliferation and metastasis in cancers. Accumulating studies have claimed that long non-coding RNAs (lncRNAs) participate in the progression of various cancers. The aim of this research is to explore the biological role and regulatory mechanism of LncRNA HOXA-AS2 in cervical cancer.Methods: Experiments including RT-qPCR, western blot, RIP, MTT, EdU, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The mean age of participants was 45.3 ± 8.7 years, and 82.7% were male. Abdominal pain was the most frequent clinical sign (100%), followed by dyspepsia(87.7%), nausea or vomiting (72.8%), and a bloated stomach (61.7%) [21]. Our statistical analysis of the general clinical symptoms of acute pancreatitis, including nausea, vomiting, abdominal pain, abdominal distension and fever, it was found that the severe group was signi cantly higher than the non-severe group (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of participants was 45.3 ± 8.7 years, and 82.7% were male. Abdominal pain was the most frequent clinical sign (100%), followed by dyspepsia(87.7%), nausea or vomiting (72.8%), and a bloated stomach (61.7%) [21]. Our statistical analysis of the general clinical symptoms of acute pancreatitis, including nausea, vomiting, abdominal pain, abdominal distension and fever, it was found that the severe group was signi cantly higher than the non-severe group (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%